PELAKSANAAN PEMBELAJARAN PRAKTIK INSTRUMEN POKOK GESEK (BIOLA) PADA MASA PANDEMI DI SMKN 12 SURABAYA - Yudha, Septian Brahmatya (Jurnal Pendidikan Sendratasik, 2024)
The COVID 19 pandemic has affected various sectors, one of which is education. This study aims to describe the implementation of the learning of the Principal String Instrument Practice (Violin) which was carried out at SMKN 12 Surabaya. Learning the Practice of String Instruments (Violin) is the object of research. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis was carried out by reducing data, presenting data, and presenting data. Data validity uses triangulation, technical triangulation and source triangulation. The results of this study indicate that the implementation of learning on the principle of string instrument practice (violin) during a pandemic at SMKN 12 Surabaya follows the health protocol, carried out by maintaining distance and wearing masks. The implementation of learning is divided into three, opening, core, and closing with a time allocation of 30 minutes. The results of the learning assessment of the principal string instrument (violin) practice showed an increase in student scores in terms of UTS and UAS scores. Thus the implementation of the learning of the principal string instrument practice (violin) is carried out well. Keywords: implementation, learning, pandemic, major practice strings instruments